Global-in-time solutions of 3-dimensional Vlasov-Poisson system - Parsa, Zohreh; Zadorozhny, V. (Вопросы атомной науки и техники, 2006)
In this paper, we consider 3-dimensional Vlasov-Poisson system and study their qualitative properties of globalin-time solutions from the point of view integrability, stability, and optimality using the concept of special constructed integral equations and the Lyapunov direct method. We provide criteria that guarantee the existence of solution for the above mentioned properties By using this approach we reduce the problem of the charged-particle beam transport, in particular, focusing with acceleration, to a problem of optimal control of dynamic system.